ORFV infection enhances CXCL16 secretion and causes oncolysis of lung cancer cells through immunogenic apoptosis - Wang, Ruixue; Mo, Jingying; Luo, Xiaoshan; Zhang, Guixian; Liu, Fang; Luo, Shuhong (Frontiers in Cellular and Infection Microbiology, 2022)
Oncolytic viruses have been emerging as a promising therapeutic option for cancer patients, including lung cancer. Orf virus (ORFV), a DNA parapoxvirus, can infect its natural ungulate hosts and transmit into humans. Moreover, the ORFV has advantages of low toxicity, high targeted, self-amplification and can induce potent Th1-like immunity. This study explored the therapeutic potential of ORFV NA1/11 infection for human lung cancer therapy and investigated the molecular mechanisms. We used a previously described ORFV NA1/11 strain and tested the oncolysis of ORFV NA1/11 in lung cancer cells in vitro and in vivo by WST-8 assay and murine models. We characterized features of cell death induced by ORFV NA1/11 through Western blot, immunohistochemistry and flow cytometry, respectively. Moreover, flow cytometry analysis was performed to determine the immune response in tumor-bearing mice with ORFV NA1/11 therapy. The results indicated that ORFV NA1/11 infection arrested cell cycle in G2/M phase, reduced cyclin B1 expression and caused lung cancer cell immunogenic apoptosis in a caspase-dependent manner. Mechanistically, ORFV NA1/11 infection of lung cancer cells induced oncolysis of tumor cells to release danger-associated molecular patterns, and promoted dendritic cells maturation, and CD8+ T cells infiltration in the tumors by enhancing CXCL16 secretion. These findings may help to understand the molecular mechanisms of ORFV oncolysis and aid in the development of novel therapies for lung cancer